A compact fiber-integrated optofluidic platform for highly specific microRNA Förster resonance energy transfer detection. Issue 14 (13th May 2021) - Feng, Hongtao; Liu, Lin; Chen, Yi; Shu, Weiliang; Huang, Yuqing; Zhang, Baoyue; Wu, Tianzhun; Jin, Zongwen; Chen, Yan
Abstract : A compact optofluidic platform was developed to perform a rapid, simple, quantitative and high-specificity miRNA assay using a novel three-way junction FRET probe. Abstract : MicroRNAs (miRNAs) have attracted extensive interest as promising biomarkers for the profiling of diseases. However, quantitative measurement of miRNAs presents a significant challenge in biochemical studies. In this work, we developed an innovative optofluidic platform to perform a rapid, simple, quantitative and high-specificity miRNA assay using the Förster resonance energy transfer (FRET) principle. A novel three-way junction FRET probe was proposed to enable rapid and enzyme-free miRNA detection. Using this platform, we performed one-step, amplification-free miRNA detection with simple device operation and achieved miRNA identification at a low concentration. The detection system could achieve high specificity for discrimination of three-base mismatches, and the sample volume was significantly reduced, favorable for low-level miRNA detection in material-limited samples. The establishment of a compact, low-cost, highly sensitive and selective miRNA analysis platform provides a valuable tool for point-of-care diagnosis.